2018
DOI: 10.1016/j.cyto.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Severity of COPD and its relationship with IL-10

Abstract: Our findings suggest that patients with severe COPD can exhibit compromised "inflammatory status", characterized by higher IL6, IL-6/IL-10 ratio and lower IL-10 concentration. Furthermore, IL-10 seems to be an interesting cytokine to be investigated in this kind of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 43 publications
3
32
0
1
Order By: Relevance
“…Few studies have investigated the role of IL-10 in the systemic inflammation of people with COPD. Similar to our results, recent studies have demonstrated that COPD people show reduced plasma levels [ 30 , 31 ]. Interleukin-10 has been shown to suppress all the proinflammatory cytokines and is effective in blocking the synthesis of IL-8 [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Few studies have investigated the role of IL-10 in the systemic inflammation of people with COPD. Similar to our results, recent studies have demonstrated that COPD people show reduced plasma levels [ 30 , 31 ]. Interleukin-10 has been shown to suppress all the proinflammatory cytokines and is effective in blocking the synthesis of IL-8 [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…31,32 Furthermore, many studies have explored the association of cytokines with the lung function of patients with stable COPD. 30,[33][34][35] Previous studies have shown correlations between plasma levels of TNF-α, IL-1β, IL-6, IL-10, IL-15, and IL-17 with the severity of bronchial obstruction. [33][34][35] Bradford et al, in a combined analysis of two large studies, including 2123 subjects from "COPDGene" and 1117 subjects from "SPIROMICS", with analysis of six cytokines (IL-2, IL-6, IL-8, IL-10, TNF-α, and IFN-γ), found an association of four biomarkers (IL-6, IL-8, and IL-10) with worse airflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the serum level of IL-10 can reduce the effects of various inflammatory factors, such as IL-6 and IL-8, and further inhibit the airway inflammatory response and airway secretions, thereby improving the ventilation function. 33 , 34 IL-35 exerts a certain inhibitory effect on inflammatory response, and it also negatively regulates the activity of immune factors, thereby improving the lung function of patients. 35 Another study suggested that IL-35 plays a role in retarding the pathogenesis of COPD by regulating the inflammatory response of Th2- and Th17-mediated COPD.…”
Section: Discussionmentioning
confidence: 99%